Effects of dissolved oxygen concentration on photosynthetic bacteria wastewater treatment: Pollutants removal, cell growth and pigments production. (October 2017) - Meng, Fan; Yang, Anqi; Zhang, Guangming; Wang, Hangyao
Graphical abstract: Highlights: This paper for the first time studied DO effects on PSB wastewater treatment. DO of 2–4 mg/L was recommended for pollutants removal. PSB biomass reached 1645 mg/L when DO concentration was 4–8 mg/L. DO > 1.0 mg/L was preferred for pigments production. Abstract: Dissolved oxygen (DO) is an important parameter in photosynthetic bacteria (PSB) wastewater treatment. This study set different DO levels and detected the pollutants removal, PSB growth and pigments production. Results showed that DO significantly influenced the performances of PSB wastewater treatment process. The highest COD (93%) and NH3 -N removal (83%) was achieved under DO of 4–8 mg/L, but DO of 2–4 mg/L was recommended considering the aeration cost. PSB biomass reached 1645 mg/L under DO of 4–8 mg/L with satisfying co-enzyme Q10 content. The biomass yield was relatively stable at all DO levels. For bacteriochlorophyll and carotenoids, DO > 1 mg/L could satisfy their production. On the other hand, DO < 0.5 mg/L led to the highest dehydrogenase activity. According to the different purposes, the optimal treatment time was different. The most pigments production occurred at 24 h; biomass reached peak at 48 h; and the optimal time for pollutants removal was 72 h.